2023
DOI: 10.1212/wnl.0000000000207458
|View full text |Cite
|
Sign up to set email alerts
|

Association of Baseline Metabolomic Profiles With Incident Stroke and Dementia and With Imaging Markers of Cerebral Small Vessel Disease

Abstract: Background and Objectives Cerebral small vessel disease is a major cause of stroke and dementia. Metabolomics can help identify novel risk factors to better understand pathogenesis and predict disease progression and severity. Methods We analyzed baseline metabolomic profiles from 118,021 UK Biobank participants. We examined cross-sectional associations of 325 metabolites with MRI markers of small vessel disease, evaluated longitudinal associations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Previous metabolomics studies have identified metabolites associated with CSVD, cerebral microbleeds, and dementia. In a large-scale metabolomics study conducted by Harshfield and Markus (2023) , they analyzed the relationships of 325 metabolites with MRI markers of CSVD (WMH, FA, and MD), stroke, and dementia, and assessed the causality of these relationships using MR approach. They found 289 metabolic traits significantly associated with MRI markers of CSVD and future risk of stroke and dementia.…”
Section: Resultsmentioning
confidence: 99%
“…Previous metabolomics studies have identified metabolites associated with CSVD, cerebral microbleeds, and dementia. In a large-scale metabolomics study conducted by Harshfield and Markus (2023) , they analyzed the relationships of 325 metabolites with MRI markers of CSVD (WMH, FA, and MD), stroke, and dementia, and assessed the causality of these relationships using MR approach. They found 289 metabolic traits significantly associated with MRI markers of CSVD and future risk of stroke and dementia.…”
Section: Resultsmentioning
confidence: 99%
“…[224][225][226] These implicate a wide range of cSVD-associated biological processes, ranging from BBB and extracellular matrix organization, to lipid and lipoprotein metabolism and immune responses. 222,224,225 The wealth of knowledge gained is not just useful for mechanistic interrogations and discovery of blood-or plasma-based diagnostic markers; it may also help us devise individual or omics-based panels of biomarkers for monitoring treatment response. Because imaging marker progression takes a relatively long time to reveal, omics or biomarker readouts that permit complementary and potentially earlier assessment of the potential impacts of drug treatment on cerebrovascular health are highly desired.…”
Section: Potential Roles Of Multiomics In Drug Trialsmentioning
confidence: 99%
“…Recent interesting works have uncovered blood epigenetic and metabolomic signatures that correlate with cSVD severity, 222,223 disease burden quantified by imaging markers, and cognitive function. [224][225][226] These implicate a wide range of cSVD-associated biological processes, ranging from BBB and extracellular matrix organization, to lipid and lipoprotein metabolism and immune responses. 222,224,225 The wealth of knowledge gained is not just useful for mechanistic interrogations and discovery of blood-or plasma-based diagnostic markers; it may also help us devise individual or omics-based panels of biomarkers for monitoring treatment response.…”
Section: Potential Roles Of Multiomics In Drug Trialsmentioning
confidence: 99%
“…Increasing research has revealed a link between metabolic alternations and CSVD. The large-scale metabolomics study and Mendelian analysis found multiple metabolites associated with imaging markers of CSVD, cognition, and conversion to dementia [ 26 28 ]. Accordingly, there may exist metabolic pathways that mediate the impact of SGLT1/2 inhibitors on CSVD progression.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing research has revealed a link between metabolic alternations and CSVD. The largescale metabolomics study and Mendelian analysis found multiple metabolites associated with imaging markers of CSVD, cognition, and conversion to dementia [26][27][28].…”
Section: Introductionmentioning
confidence: 99%